In Silico Study Of Natural Bioactive Compounds As Potential Anti-Mpox Through Molecular Docking On D13 Protein - Anastasia Maria Angelica Montolalu; Angelina Stevany Regina Masengi; Jimmy Posangi; Trina Ekawati Tallei; Fatimawali; Christi Diana Mambo; Dian Augina Rintibulawan Rambulangi (JURNAL BIOS LOGOS, 2025)
Mpox is a zoonotic disease caused by Monkeypox virus (MPXV), with a surge in cases posing a major challenge due to the unavailability of specific antivirals. Indonesia's biodiversity offers great opportunities for the exploration of bioactive compounds from natural materials as therapeutic alternatives, especially by targeting the D13 protein, which is an essential structural protein in MPXV. This study aims to evaluate the interaction and affinity of molecular tethering of bioactive compounds to D13 protein and analyse the physicochemical, pharmacokinetic and toxicity profiles of the compounds. The research was conducted using molecular tethering method using Gnina software on Google Colab platform. Antiviral activity prediction was performed using PASS Online, followed by Lipinski's Rule of Five (RO5) evaluation and pharmacokinetic and toxicity analysis using SwissADME and pkCSM. The results showed that the tested bioactive compounds had good potential antiviral activity and fulfilled the RO5 criteria. Pharmacokinetic and toxicity analyses indicated good pharmacokinetic profiles but poor metabolic profiles, with predicted low toxicity levels, supporting the feasibility of these compounds to be further developed as therapeutic candidates. In addition, the bioactive compound showed the ability to interact with D13 protein with the best affinity tethering value of myricetin with a free binding energy (ΔG) value of -8.37 kcal/mol, making it a potential candidate as an antiviral for Mpox.